School leadership in a diverse society : helping schools prepare all students for success - McCray, Carlos R.; Beachum, Floyd D.; Reggio, Phyllis F. (Educational leadership for social justice., 2021)
"With the increasing amount of diversity taking place in the United States and in our K-12 schools, this book will ask whether school leaders are prepared. It is the school principal who sets the tone for the school culture and provides the vision as to the direction of the organization. Therefore, school principals will ultimately have the greatest impact in promoting cultural and social diversity. School Leadership in a Diverse Society: Helping Schools Prepare all Students for Success (2nd Edition) will help scholars and practitioners have a better understanding of the increasing amount of diversity that is occurring in American society. This book will give them the tools needed to lead schools to ensure that all students, regardless of their life circumstances and status, are provided a school experience that promotes high academic achievement and a sense of belonging. Today, multiculturalism and diversity preparation are needed in our society, seemingly more so than when schools first made an earnest effort to integrate twenty years after Brown V. Board of Education. Just as it seemed the United States was making significant progress dealing with issues that have plagued this country for hundreds of years, recently, there have been a resurgence of issues (immigration debate, Charlottesville, VA protests, blackface incidents, increased wealth divide between races, religious backlash, etc.,). These issues should remind us that the struggle for social equity continues in the present moment to help fight intolerance and prejudice within our country and schools"--